The Implementation of Problem Based Learning Model to Improve Students Activities in Citizenship Education Subject - Heri Usmanto; Sundari Utami; Alif Aditya Candra; Siti Tiara Maulia (Indonesian Journal of Social Science Education (IJSSE), 2025)
Problems in classroom learning are becoming more complex day by day, especially regarding the final results in learning activities that will be achieved. This is caused by several factors in teaching and learning activities which are not optimally implemented by teaching staff or lecturers. Lecturers have a very important role in achieving the success of their students or students. But in reality, when studying citizenship, students do not appear active in participating in the teaching and learning process in class, the class only looks monotonous, with the lecturer playing an active role, students only listen and do not play a role. active in the learning process. In situations like this, creativity is needed from a lecturer or teaching staff to stimulate student activity in participating in the learning process so that the learning process does not only go in one direction but there is reciprocity between lecturers and students. In order for learning to occur in a class where students are actively involved, the lecturer or teacher must use an interactive model or method such as using a cooperative model. In teaching this citizenship course, researchers use the problem based learning (PBL) learning model.The aim of this research is to find out how the learning activities of Pancasila and Citizenship Education (PPKn) students class of 2023 in the Citizenship course use the Problem Based Learning (PBL) model. The research method used by the researcher is the classroom action research method which applies research stages using cycles, where in the research it is planned to carry out three cycles consisting of three face-to-face meetings in each cycle. With each cycle using the steps or syntax of the PBL model.  The results obtained in the research were an increase in student activity after participating in classroom learning using the method applied by the lecturer using the PBl model. This can be seen from the results of learning activities in cycles I, II and III showing significant improvement from cycles I, II and III.